Young children perceptions in 3D construction tasks - Alves, Cristina da Silva (2012)
As part of a broader investigation, aiming at analysing in what ways the visual abilities are worked on, both in preschool and first grade and how children exhibit those abilities, clinical interviews with 16 children ages 3 to 7 have been conducted in order to find out how they perceive, compare and reproduce colourful blocks constructs. In this paper we present results related to two of the proposed tasks: one involving the reproduction of a construction with color cubes and the other concerning the identification of different views of a construction.